2016
DOI: 10.1016/j.marpolbul.2016.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metal pollution on shrimp Crangon affinis by NMR-based metabolomics

Abstract: a b s t r a c t a r t i c l e i n f oBoth cadmium and arsenic are the important metal/metalloid pollutants in the Bohai Sea. In this work, we sampled the dominant species, shrimp Crangon affinis, from three sites, the Middle of the Bohai Sea (MBS), the Yellow River Estuary (YRE) and the Laizhou Bay (LZB) along the Bohai Sea. The concentrations of metals/metalloids in shrimps C. affinis indicated that the YRE site was polluted by Cd and Pb, while the LZB site was contaminated by As. The metabolic differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…In the mussels collected from the Bohai Sea in China, a survey reported that the mussels from some of the sampling sites were polluted by Cd and As with average concentrations at~2 and 5 mg/L, respectively [2]. In our recent study, the Cd and As pollution have been confirmed by the high accumulations of Cd and As in marine shrimp Crangon affinis collected from the Yellow River Estuary and Laizhou Bay along the Bohai coast, respectively [3]. Although Cd is relatively rare in marine environment, the concentration of Cd has reached 50 mg/L in some heavily polluted estuaries or harbors and ports [4].…”
Section: Introductionmentioning
confidence: 72%
“…In the mussels collected from the Bohai Sea in China, a survey reported that the mussels from some of the sampling sites were polluted by Cd and As with average concentrations at~2 and 5 mg/L, respectively [2]. In our recent study, the Cd and As pollution have been confirmed by the high accumulations of Cd and As in marine shrimp Crangon affinis collected from the Yellow River Estuary and Laizhou Bay along the Bohai coast, respectively [3]. Although Cd is relatively rare in marine environment, the concentration of Cd has reached 50 mg/L in some heavily polluted estuaries or harbors and ports [4].…”
Section: Introductionmentioning
confidence: 72%
“…Sun et al reported that Cd posed prominent risk on the marine organisms and ecosystem due to the high concentrations of Cd in the sediments from the Bohai coast [1]. Our recent research indicated that the dominant species, shrimp Crangon affinis, was contaminated by Cd from the Yellow River Estuary along the Bohai Sea [2]. As it is known, Cd can induce multiple adverse effects in organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that chronic As exposure perturbed amino acids metabolism . Decreased level of tyrosine caused by As exposure were reported in serum of rats, and in tissues of marine animals, and that tyrosine can be biomarker of As contamination in shrimp Crangon affinis . However, similarly, our previous study showed that tyrosine augmented in cerebral cortex after 12‐week As exposure, and that there were differences between cerebral cortex and serum metabolomics .…”
Section: Disscusionmentioning
confidence: 59%